Pengaruh Beban Kerja, Klien Baru, Dan Ukuran Klien Terhadap Defisiensi Audit - Yoga, Budhi Setiya; Dinarjito, Agung (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 1 (2019)DO - 10.24843/JIAB.2019.v14.i01.p09, 2019)
This study aims to examine whether public accountants’ workload, new clients, and size of clients influence the occurrence of audit deficiencies conducted by public accountants on the basis of the data collected by the Finance Professions Supervisory Centre (PPPK), Ministry of Finance. PPPK is given the authority to ensure that the audits carried out by public accountants are in accordance with applicable standards. This is a quantitative research using multiple linear regression analysis of public accountants’ data examined by PPPK from 2013 to 2016. Test results show that only the client size affects the audit deficiencies identified by PPPK in a positive direction. This research is expected to be a resource for public accountants to give proper attention during audits of large clients and help PPPK in determining the examination samples of public accountants each year. Keywords : audit, audit deficiency, PPPK, public accountant